ANALISIS WORDWALL BERBANTUAN IFP DALAM PEMBELAJARAN MEMBACA PEMAHAMAN TEKS CERITA - Wulandari, Ayu; Kusuma Putri, Mega; Hetilaniar (STKIP Subang, 2026)
This study aims to analyze the effectiveness of using interactive media, Wordwall, integrated with Interactive Flat Panel (IFP), in improving reading comprehension skills in narrative texts. The primary motivation for this research was low reading interest and students' difficulties in understanding the intrinsic elements of texts. The method used was descriptive qualitative, with data collection through observation and interviews. The results showed that the combination of Wordwall and IFP created a dynamic and visual learning environment, enabling students to more easily construct meaning from narrative texts. The conclusion of this study is that the appropriate use of interactive technology can be an innovative solution to address literacy barriers in elementary schools.